Drugs or Surgery? For Control of Type-2 Diabetes Mellitus (Journal of Chittagong Medical College Teachers' Association, 2014)
Type 2 diabetes is one of the fastest growing epidemics in human history and is usually related to obesity [1]. The condition is not very uncommon in non obese person [2]. Tight glycemic control with medication (HbAlc less than 7%) has been shown to decrease the risk of micro vascular complications like retinopathy, nephropathy, and neuropathy, associated with diabetes in 2 large randomized studies (United Kingdom prospective diabetes study, UKPDS, and diabetes control and complications trial, DCCT) [3,4]. Both studies showed that for drop of 1% (ie, from 9% to 8%) HbAlc there was a relative risk reduction of 25% to 45%. Glycemic control to achieve a HbAlc 7% in some of these patients was only possible with insulin doses > than 100 units per day and even then for only short periods of time [3]. It is believed that in community settings where >95% of diabetic patients are treated, that HbAlc levels in T2DM patients typically vary from 8.5 to 9% suggesting that tight control with medication is difficult to achieve [3]. Furthermore, intensive medical therapy required to achieve a HbAlc < 7% has a corresponding 2%-4% yearly incidence of severe hypoglycemia and often death.  So we need persistent glycemic control but method must be safer."And so it is. Just as Walter Pories said, we surgeons were unprepared to adequately assess the observation that gastric bypass surgery cured type 2 diabetes mellitus (IIDM)”. The scenario was observed by Friedman MN.et.al in the year 1955 in patients that underwent subtotal gastrectomies [5]. But the massage not only draws attention, also initiates debate among endocrinologist, surgeons and physicians.It was again observed in 1982 after remission of diabetes for the first time following a gastric bypass [6]. However, its practical importance was never valued until introduction of bariatric surgery, in which surgery done to reduce body weight.JCMCTA 2014 ; 25 (1): 1-2